Pengaruh Job Satisfaction Dan Self Efficacy Terhadap Job Performance Pada Karyawan PT Tanjung Baru Kalimantan Selatan - Monica Cicilia Romana Siregar; Bachrudin Ali Akhmad; Emy Rahmawati (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
This study aims to partially prove and analyze the effect of Individual Characteristics, Job Characteristics, Organizational Characteristics on Employee Performance, and the effect of Individual Characteristics, Job Characteristics, Organizational Characteristics on Employee Performance simultaneously at PT. Jasapower Indonesia in Tabalong Regency. The approach used in this research is quantitative, with the type of causality associative research. The sampling method used nonprobability sampling with saturated sampling method on 40 employees of PT Jasapower Indonesia. The google form questionnaire was distributed via Whatsapp to each respondent. Data analysis using multiple linear analysis test and data calculation using SPSS 22. The results of the study found that Individual Characteristics, Job Characteristics and Organizational Characteristics had a positive and significant effect partially and simultaneously on the Employee Performance of PT. Jasapower Indonesia. The results of this study are useful as material for consideration, performance evaluation and input in preparing organizational programs and policies, especially regarding human resources.  Keywords: Individual Characteristic, interest, Job Characteristics, Autonomy, Job Variety, Organizational Characteristics, Organizational Climate, Employee Performance, Quality